KOMPOSISI HASIL TANGKAPAN PERIKANAN TUGU DI PERAIRAN KOTA TARAKAN - Rizal, Agus; Laga, Asbar (Jurnal Harpodon Borneo, 2012)
Tugu fishing gear is one type of fishing gear in the city of Tarakan. Tugu fishing gear is highly dependent on the tides (tidal trap). In specification-pillar dimension of fishing gear catches indicated that generated diverse in type and size. This study aims to determine the types of fisheries catches the trap and the composition of fishery catches the existing tugu in the town of Tarakan. samples are taken from three stations, among others; station 1 is located in The Village Mamburungan precisely in Cape sand, station2 and station 3 is located in The Village Beach charity. Total catch weight of 12 528 heads with 54.2 Kg. The identification results obtained during the investigation of 34 species from six groups of species of marine life. Highest composition based on the number during the experiment shows in a row is a freckle-pink shrimp (Metapenaeus sp) amounted to 49.79%., And the lowest was Goldstripe sardinella (sardinella Fimbriata), chacunda gizzard (dorosoma chacunda), giant catfish (Arius thalassinus), yellowpike (Congresox talabon), Halibut (psettodes erumei), mackerel (Scomberomorus guttatus), and sea snake (Enhydrina Schistosa) 0.01% respectively. Keywords: composition, fishery catches trapt, and the City of Tarakan